Distally Based Sural Faciocutaneous and Fascial (Adipofascial) Flap for Reconstruction of Distal Leg, Ankle and Foot Defects - Parajuli, NP; Shrestha, D; Panse, N (Kathmandu University Medical Journal, 2015)
Background Any soft tissue defect in distal leg, ankle and hind foot is still a challenging problem. There are various options for coverage of such defects, but the distally based sural neurocutaneous and neurofascial flap based on the sural nerve and superficial sural artery has been an important option.Objective To evaluate the efficacy of distally based sural flap in reconstruction of the distal leg, ankle and hind foot soft tissue defects.Method Seventeen patients with soft tissue defects over distal leg, ankle and hind foot were included in this study. All patients were treated with distally based sural flap. Most of the cases were due to trauma (16 cases) which compromised tendon and bone. One case was of malignant melanoma of sole of hind foot which required wide excision and soft tissue reconstruction with sural flap.Result In all cases defects were successfully covered. Three showed venous congestion and partial necrosis. One developed secondary infection. One flap failed completely. Mean follow up of patients was 20 months (6 – 36 months).Conclusion Sural flap is a good option for reconstruction of distal leg, ankle and foot defects.Kathmandu University Medical Journal Vol.12(2) 2014: 126-131